Detailed Electronic Structure, Physico-Chemical Properties, Excited State Properties, Virtual Bioactivity Screening and SERS Analysis of Three Guanine Based Antiviral Drugs Valacyclovir HCl Hydrate, Acyclovir and Ganciclovir. (21st April 2022) - Al-Otaibi, Jamelah S.; Mary, Y. Sheena; Thomas, Renjith; Kaya, Savaş
Abstract: Valacyclovir HCl hydrate, acyclovir and ganciclovir are three commonly used anti viral drugs which are guanidine derivatives with ether side chain and all of them act by interfering with the viral DNA production. This manuscript tries to examine the structure and properties of these three purine based compounds using electronic structure methods and molecular mechanics. Density functional theory was used to optimize the ground state geometry of the molecules from frontier molecular orbitals are analyzed using B3LYP functional. They give wealth of information about the electronic properties and descriptors, which will enable to predict the bioactivity of the molecules. As the electrons interact with electromagnetic radiations, electronic excitations between different energy levels are analyzed in detail using TD-DFT with CAM-B3LYP orbital. Calculations shows that they are with excellent light-harvesting efficiency hence be used as photo sensitizers. Molecular docking studies predict the biological activity of the molecules against ADP-thymidine kinase, hence inhibits its action, subsequently affecting the viral DNA production. It is interesting to see that on adsorption with a graphene quantum dot surface, all adsorbed complex show enhancement in the Raman activity giving Surface Enhanced Raman Spectra (SERS) when studied using dispersion force corrected ω-B97XD functional. This can be used for the detection of these drugs in a pharmacological or biological sample. Interestingly the graphene drug molecular assembly shows enhanced biological activity when compared to individual drug molecules.